THE SIGNIFICANCE OF DIGITAL CULTURE IN THE WORK OF EDUCATORS EMPLOYED IN VOCATIONAL EDUCATION INSTITUTIONS (Innovative professional education, 2023)
The article addresses the topic of digital culture and its significance in the work of educators in vocational education institutions. It explores the importance of digital culture in the professional growth of teachers, its effects on the quality of teaching and learning, and the difficulties teachers encounter when integrating digital tools and technologies in their practice. Additionally, it emphasizes the advantages of digitalization in education.
Keywords: digital culture, pedagogical worker, activity, professional development, vocational education institutions